2009
DOI: 10.1111/j.1423-0410.2009.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen reduction technology (Mirasol®) treated single‐donor platelets resuspended in a mixture of autologous plasma and PAS

Abstract: In comparison to PRT platelets resuspended in 100% plasma, a mixture of plasma and PAS improves pH and platelet metabolism but not platelet activation. Prolonged shelf-life for up to 7 days may be possible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
5
31
1
2
Order By: Relevance
“…164,165 Pathogen reduction technologies (e.g., psoralen-based UV treatment) can reduce contamination risks, but so far these have extended the PC shelf-life only marginally. [165][166][167][168] Several other platelet-derived products are currently under investigation, e.g., frozen (−80 C) platelets, cold-stored (4 C) platelets, lyophilized platelets, platelet-derived microparticles and infusible platelet membranes (IPM), and trehalose-stabilized platelets (Thrombosomes; Cell-Phire, Rockville, Maryland, USA), with a vision to extend shelf-life of platelet-based hemostatic products without compromising biofunctional properties. [169][170][171][172] PCs and natural platelet-derived products are usually obtained from pooled blood of multiple donors, and this presents significant risks of blood-borne infection that, in turn, necessitates rigorous serological testing and expensive leukoreduction techniques.…”
Section: Platelet Substitutes Synthetic Hemostats and Platelet-inspmentioning
confidence: 99%
“…164,165 Pathogen reduction technologies (e.g., psoralen-based UV treatment) can reduce contamination risks, but so far these have extended the PC shelf-life only marginally. [165][166][167][168] Several other platelet-derived products are currently under investigation, e.g., frozen (−80 C) platelets, cold-stored (4 C) platelets, lyophilized platelets, platelet-derived microparticles and infusible platelet membranes (IPM), and trehalose-stabilized platelets (Thrombosomes; Cell-Phire, Rockville, Maryland, USA), with a vision to extend shelf-life of platelet-based hemostatic products without compromising biofunctional properties. [169][170][171][172] PCs and natural platelet-derived products are usually obtained from pooled blood of multiple donors, and this presents significant risks of blood-borne infection that, in turn, necessitates rigorous serological testing and expensive leukoreduction techniques.…”
Section: Platelet Substitutes Synthetic Hemostats and Platelet-inspmentioning
confidence: 99%
“…Although the introduction of PRT may negate the need for platelet irradiation, bacterial testing and additional donor screening tests, several aspects of in vitro platelet quality or function appear to be affected. A number of studies have concluded that the M‐PRT system exacerbates the effects of the platelet storage lesion [3–7]. However, in most cases, although significant, the in vitro changes to these platelet parameters are within the normal limits of acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have concluded that Mirasol treatment exacerbates the effects of the platelet storage lesion, resulting in increased glucose consumption, lactate production, and increased markers of platelet activation [2,3,4,5,6]. Further, we and others have previously demonstrated that Mirasol treatment affects platelet signal transduction and apoptotic protein expression [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%